Eus-Pancreaticogastrostomy in a Patient with Subtotal Gastrectomy and Roux-En-Y Reconstruction - Mutignani Massimiliano; Dioscoridi Lorenzo; Forti Edoardo; Pugliese Francesco; Manta Raffaele (Pancreas, 2025)
Chronic Pancreatitis (CP) is often associated with pain due to pancreatic duct ob-struction. In these patients, surgical drainage was more effective than endoscopic treatment, achieving a faster, effective, and sustained pain relief.1 However, when surgery is not suitable, different endoscopic procedures could be performed. Endoscopic drainage usually requires transpapillary access to the pancreatic duct during Endoscopic Retrograde Cholangio-Pancre-atography (ERCP). The main limitation of endoscopic procedure is that the pancreatic duct could not be accessible at ERCP because of Roux-en-Y reconstruction after gastric-pancreatic surgery. Interventional Endoscopic Ultrasound (EUS) may allow a successful drainage of a dilated pancreatic duct, by using an endoscopic cysto-enterostomy followed by stent place-ment. We described the EUS-pancreaticogastrostomy performed in a patient who underwent a subtotal gastrectomy complaining with chronic pancreatitis.